Duration of Weed Presence Influences the Recovery of Photosynthetic Efficiency and Yield in Common Bean (Phaseolus vulgaris L.) - McKenzie-Gopsill, Andrew G.; Amirsadeghi, Sasan; Fillmore, Sherry; Swanton, Clarence J. (Frontiers in Agronomy, 2020)
Photosynthetic responses of common bean (Phaseolus vulgaris L.) to increasing durations of weed-free and weedy environments were investigated using a critical period for weed control study under field conditions. The presence of weeds induced the shade avoidance response and was accompanied by a reduced red to far-red ratio (R/Fr) of reflected light supporting previous assertions it is an important signal regulating crop-weed interactions. Despite increases in stomatal conductance and leaf intercellular [CO2] with increasing duration of weed presence, CO2 assimilation and photosynthetic efficiency continually declined. This coincided with reduced Calvin cycle capacity suggesting induction of biochemical rather than stomatal limitations on photosynthesis. Weed removal prior to reproductive stages resulted in maintenance of high photosynthetic capacity. When weed presence extended to reproductive stages and beyond the critical period for weed control, however, CO2 assimilation and photosynthetic efficiency never recovered. Yield was highly correlated with photosynthetic efficiency and in a similar manner, declined with increasing durations of weed presence through reduced seeds per plant. We conclude that the lasting consequence of weed competition is impairment of photosynthesis, which may provide an important mechanism to explain yield loss.